Low‐Altitude High‐Latitude Stratospheric Aerosol Injection Is Feasible With Existing Aircraft - Alistair Duffey; Matthew Henry; Wake Smith; Michel Tsamados; Peter J. Irvine (Earth's Future)
Abstract Stratospheric aerosol injection (SAI) is a proposed method of climate intervention in which aerosols or their precursors would be injected into the stratosphere to reduce or halt global warming. It is often assumed that to produce a substantial global cooling, SAI would require a fleet of specially designed high‐altitude aircraft. However, in the extra‐tropics, where the tropopause is lower, injection into the stratosphere using existing large jets is plausible. Here, we simulate an ensemble of 41 short stratospheric aerosol injection simulations in the UK Earth System Model in which we vary the altitude, latitude, and season of SO2 injection. For each simulation, we diagnose aerosol optical depth and radiative forcing and estimate the global cooling under a sustained deployment. For altitudes up to around 14 km, high‐latitude injection maximizes global forcing efficiency. Aerosol lifetime variation is the largest contributor to changes in efficiency with injection location. Seasonal SAI deployment with low‐altitude (13 km) and high‐latitude (60°N/S) injection achieves 35% of the forcing efficiency of a high‐altitude (20 km), annually constant, sub‐tropical (30°N/S) strategy. Low‐altitude high‐latitude SAI would have strongly reduced efficiency and therefore increased side‐effects for a given global cooling. It would also produce a more polar cooling distribution, with reduced efficacy in the tropics. However, it would face lower technical barriers because existing large jets could be used for deployment. This could imply an increase in the number of actors able to deploy SAI, an earlier potential start date, and perhaps a greater risk of unilateral deployment.